Հայ-ֆրանսիական հարաբերությունների կայացումն ու զարգացումը (1991-2015 թթ.) - Հ. Գ. Ղուլյան (ՀՀ ԳԱԱ հրատ.)
В результате весьма успешных переговоров и достигнутых за столько лет договоренностей, а также политического диалога между двумя странами установились теплые дружественные и доверительные отношения. Официальные визиты способствовали обсуждению многих политических вопросов. Армяно-французский политический диалог ведется на довольно высоком уровне, содействуя прогрессу переговорного процесса по урегулированию Карабахского конфликта в формате Минской группы. Studying the history and content of the Armenian-French relations, it can be concluded about the importance of the official visits and negotiations on a regular basis. As a result of quite successful negotiations and reached agreements for so many years and also the political dialogue, the two countries have established a good friendship and relations based on mutual trust. Visits contributed to the discussion of political issues. The Armenian-French political dialogue is at a fairly high level, contributing to the progress of the negotiation process of the settlement of the Karabakh Conflict in Minsk Group format.
Keywords: History; Political Science; Modern History; D History; J Political Science